Active retreat of a Late Weichselian marine‐terminating glacier: an example from Melasveit, western Iceland. (31st January 2018) - Sigfúsdóttir, Thorbjörg; Benediktsson, Ívar Örn; Phillips, Emrys
Abstract : Large and complete glaciotectonic sequences formed by marine‐terminating glaciers are rarely observed on land, hampering our understanding of the behaviour of such glaciers and the processes operating at their margins. During the Late Weichselian in western Iceland, an actively retreating marine‐terminating glacier resulted in the large‐scale deformation of a sequence of glaciomarine sediments. Due to isostatic rebound since the deglaciation, these formations are now exposed in the coastal cliffs of Belgsholt and Melabakkar‐Ásbakkar in the Melasveit district, and provide a detailed record of past glacier dynamics and the inter‐relationships between glaciotectonic and sedimentary processes at the margin of this marine‐terminating glacier. A comprehensive study of the sedimentology and glaciotectonic architecture of the coastal cliffs reveals a series of subaquatic moraines formed by a glacier advancing from Borgarfjörður to the north of the study area. Analyses of the style of deformation within each of the moraines demonstrate that they were primarily built up by ice‐marginal/proglacial thrusting and folding of marine sediments, as well as deposition and subsequent deformation of ice‐marginal subaquatic fans. The largest of the moraines exposed in the Melabakkar‐Ásbakkar section is over 1.5 km wide and 30 m high and indicates the maximum extent of the Borgarfjörður glacier. Generally, the other moraines in the series become progressively younger towards the north, each designating an advance or stillstand position as the glacier oscillated during its overall northward retreat. During this active retreat, glaciomarine sediments rapidly accumulated in front of the glacier providing material for new moraines. As the glacier finally receded from the area, the depressions between the moraines were infilled by continued glaciomarine sedimentation. This study highlights the dynamics of marine‐terminating glaciers and may have implications for the interpretation of their sedimentological and geomorphological records.